Main ecosystems used as native pasture in Brazil: a review (Research, Society and Development, 2020)
Native pastures have a greater potential in relation to the maintenance of biodiversity, besides presenting high adaptability to the climate conditions of each biome, but to obtain high productive rates, they require adequate agricultural management, so that land degradation decreases and pasture resilience increases. Due to the great diversity regarding the set of animal and plant life, Brazil contains six biomes, where much of the natural pastures have already been altered because of burning and deforestation, in order to originate plantations of large crops and cultivated pastures. Considering the worldwide influence of Brazilian livestock, this narrative review was carried out with the objective of verifying the relevance and potential of the main native pastures of Brazilian biomes, besides highlighting the importance of their preservation, being, therefore, a viable alternative its use as fodder.